Antecedents to firm performance during re-internationalization. Issue 3 (August 2022) - Ali, Salman; Mathur, Ajeet N; Jaiswal, Anand Kumar
There is a paucity of research on re-internationalization, where firms re-enter international operations after complete withdrawal from previous international operations. The extant literature is largely silent on what drives firm performance during re-internationalization. We conducted an empirical investigation of re-internationalized enterprises from India to identify key antecedents to firm performance during the re-internationalization phase. Data analysis using partial least squares structural equation modeling (PLS-SEM) indicates that initial internationalization experiences, presence of dynamic capabilities, and organizational commitment to internationalization positively contribute to re-internationalization performance. The findings have implications for firm strategies, organization systems, managerial attention to knowledge management, policies supporting subventions, and for future research into de-internationalization and re-internationalization. JEL Classification: F23